Tradisi “Rajah”: Terapi Mistik Dalam Kepercayaan Masyarakat Suku Jawa di Kabupaten Ogan Komering Ulu Timur - Bayu Pamungkas; Muhammad Noupal; Murtiningsih Murtiningsih; Nur Fitriyana (Jurnal Studi Agama, 2022)
This paper examines the rajah tradition in the beliefs of the Javanese people in the Ogan Komering Ulu Timur. This research is a fieldresearch using qualitative methods. Research data obtained through observation and interviews. Meanwhile, in analyzing the data of this study using descriptive-analytical techniques. This study found that there were seven rajahs used by the community; penglaris tattoo, leather tattoo, vest tattoo, tembang liring tattoo, fence tattoo, belt tattoo, and ring tattoo. The seven tattoos are believed by the Javanese community of Gunung Mas village, Belitang district, Ogan Komering Ulu Timur district to provide alternative solutions to the problems they face. The author also finds that the process of making the tattoo is based on the books of Syamsul Ma'arif and Tajul Muluk, with the following procedure; holy from hadast large and small, holding breath and praying to Allah, solemn, the writing of the tattoo is written neatly. Based on these findings, the authors conclude that belief in rajah can change fate, boost success, healing, and self-security is a form of shirk. However, if the tattoo is believed to be only a medium or a means of asking Allah SWT with the aim of asking for His help for various difficulties experienced, it is an act that is allowed in Islamic teachings, because this kind of belief leads to faith and devotion to Allah. Keywords: Rajah Tradition, Mystical Therapy, Java Society